Factors that influence the parents perspective of allowing their children to walk to / from school- an overview - Nasradeen A. Khalifa (Penerbit Universiti Kebangsaan Malaysia, 2023)
Walking is claimed as the best mode to school due to its benefits towards the environment and health. In the past, walking to school was a common mode. Nowadays, the safety and environmental issues, however, become decisive factors that prevent the parents to allow their children from walking. Despite its advantages, several investigations have shown that walking as a mode choice continues to suffer from narrow and weak foundations that impede to provide a unified identification of factors affecting the parents’ decision on walking as a mode choice. Addressing this issue, this article aims to provide a review of previous study on regards the factors affecting the parents’ decision to allow their children to walk to/from schools, the limitation of review is that the review was conducted on the published studies between 1995 and January 2019. The contribution identifies some factors affecting the parents’ decision about walking to school. It conceptualizes the relationship between different factors that affecting on parents’ decision. Out of 310 research articles 112 of them were the key of achieving the research objective as to element the founding that factors such as distance, safety, traffic, sidewalks, built environment, demography, and parents’ perception have a great influence on parents’ decision to allow their children to walk to-and-from school. The findings of this review can be used to offer a better deal with parents’ concern about their children to travel actively and safely to school. Keywords: Commuting mode choice, distance, safety, built environment, parent’ perception, public transportation.